Decoy Effect on Consumers' Purchase Behaviors in Relation to Meat Products: Comparison of Pork and Chicken - Xu, Lingling; Yu, Meidan; Chen, Xiujuan (Frontiers in Psychology, 2021)
Few studies have analysed the behaviours of consumers in relation to their purchase of meat products produced with animal welfare in consideration under different decoy scenarios; thus, it is difficult to accurately understand consumer behaviours and reduce the bias in current research conclusions regarding consumption preferences in relation to meat products that had been produced with animal welfare in consideration. With the frequent occurrence of cases connected with the quality and safety of meat in China, the welfare conditions of livestock and poultry urgently need to be improved. We used 810 consumers in Wuxi City, Jiangsu Province, China as our study sample, chose pigs and chickens, two common species of livestock and poultry, as study cases, and set four types of decoy scenarios based on breeding time, breeding model, diet cleanliness label, and price attributes, to explore consumers’ purchasing options for meat produced with high levels of animal welfare, under different decoy conditions. A decoy effect was observed in a bounded rational consumption situation in relation to both chicken and pork purchasing behaviours. In a chicken purchase situation, the decoy effect of the breeding model was the strongest, followed by that of price, diet cleanliness label, and breeding time. In the case of pork purchase, the decoy effect of the diet cleanliness label was the strongest, followed by price, breeding model, and breeding time. In a comprehensive comparison between the two types of consumption experiments, price decoy constantly played a significant role, while the decoy effect of breeding time was the weakest. Accordingly, we propose that in addition to strengthening people’s knowledge of the welfare of livestock and poultry, designing a breeding model decoy or price decoy in the process of chicken sales, and designing a diet cleanliness label decoy or price decoy in the process of pork sales can guide consumers’ demand for meat produced with high levels of animal welfare. The welfare of livestock and poultry should thus be improved.